Enhanced Antimicrobial Effect of Biosurfactant Coated Copper Nanoparticles against Selected Plant Pathogens - Dhanashree Vinayak Deshmukh; Hanumantrao Vitthal Deshmukh; Masidd Khalate (The Bioscan, 2025)
Due to their therapeutic and antibacterial uses, copper nanoparticles have gained popularity in antibacterial research. Copper nanoparticles (CuNPs) are becoming a more accessible and reasonably priced medical tool. When coated with the correct surfactant, copper nanoparticles are recognised for their antibacterial and other therapeutic qualities. Two biosurfactants, which are synthesised using ascorbic acid and obtained from culture broth from specific bacterial isolates A. xylosoxidans (P5C) and P. aeruginosa (P11), were employed in this work as capping agents for the coating of CuNps. The synthesised copper nanoparticles were characterised by UV visible spectroscopy, which showed an absorption peak at 222 nm. FT-IR analysis revealed that copper oxides (CuO) were present in each of the samples that were being examined. The zeta potential of CuO+P5C NPs is -24.1 mV, whereas that of CuO+P11 NPs is -12.1 mV, indicating the stability of the synthesised particles. The TEM and SEM examinations revealed that the irregularly sized particles had a spherical shape. An EDX analysis revealed that the sample had higher oxygen and copper. In a similar vein, morphological analysis was finished. Both types of CuNPs have shown good antimicrobial activity against the selected plant strains with minimum inhibitory concentration (MIC) value of 125 μg/ml concentration.